Regional economic integration in the Eurasian Economic Union: theory, lessons from the past and new opportunities - L. V. Shkvarya (Управление)
The article shows that the processes of world development initiate changes in various areas of international cooperation both at the global and regional levels. This is also happening within the framework of regional economic integration cooperation. The author proves that the modern transformation of integration processes has an impact on the development of the Eurasian Economic Union (EAEU). This process requires a comprehensive theoretical analysis and systematization. The purpose of the article is to analyze and evaluate integration processes in the EAEU. The scientific novelty of the article is the systematization of new phenomena and characteristics in regional economic integration in the world in the 21st century. The author also tries to formulate new tasks for the EAEU in building a progressive integration process. Another point of view, which the author substantiates in the article, is that the foundation for the development of integration in the EAEU should be taking into account ongoing global changes, previous experience of economic integration within the framework of the Council for Mutual Economic Assistance (Comecon) and the development of industrial cooperation between the EAEU countries and non-regional partners both in industry, and in agriculture, that means, in the real sectors of the economy. The author concludes that it is production cooperation in the real sectors of the economy in the EAEU that will ensure the necessary stability of both national economies and the progressive development of the integration process in the current conditions of the world economic process increased turbulence and the global system transformation. And since the EAEU faces such large-scale and vital tasks, then, according to the author, a reassessment and some redirection of integration efforts are required. It is on this basis that an adequate formation of new principles of financial cooperation in the EAEU is possible.